M2 Macrophages Promote PDGFRβ+ Pericytes Migration After Spinal Cord Injury in Mice via PDGFB/PDGFRβ Pathway - Ziyu Li; Meige Zheng; Shuisheng Yu; Fei Yao; Yang Luo; Yanchang Liu; Dasheng Tian; Li Cheng; Juehua Jing (Frontiers Media S.A., 2021)
Platelet derived growth factor receptor β positive (PDGFRβ+) pericytes form fibrotic scar, which prevents axonal regeneration after spinal cord injury (SCI). However, the mechanism by which PDGFRβ+ pericytes migrate to the injury core is unclear. Here, we investigated the effect and mechanism of macrophages polarization on PDGFRβ+ pericytes migration after SCI. Macrophages were closely related to the spatiotemporal distribution of PDGFRβ+ pericytes in the injury core at 3, 7, and 14 days postinjury (dpi). Macrophages appeared M2 polarization at 3 and 7 dpi while M1 polarization at 14 dpi. The expression of platelet derived growth factor B (PDGFB) was significantly increased after SCI and after macrophages M2 polarization. The promoting effect of exogenous PDGFB and M2 macrophages conditioned medium on PDGFRβ+ pericytes migration could be blocked by SU16f, a PDGFRβ specific inhibitor. These findings indicate that M2 macrophages can secrete PDGFB acting on PDGFRβ to promote PDGFRβ+ pericytes migration, which can be blocked by a PDGFRβ specific inhibitor SU16f. The PDGFB/PDGFRβ pathway is a promising new target for the treatment of SCI.